Profil Literasi Matematika Ditinjau Dari Gaya Kognitif Dan Gaya Belajar Pada Siswa Kelas VIII SMP Buq’atun Mubarakah - Hilal, Nurul; Rasul, A. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Mathematics is an intellectual need that is unique in modern world as well as one of the subjects taught at school which has a very vital role because it can increase students' knowledge in thinking logically, rationally, critically, carefully, effectively, and efficiently. Currently, the mathematics skills of students in Indonesia are still of great concern. The results of the PISA (Program for International Student Assessment) research in 2015 showed that the mathematical literacy skills of Indonesian students are still very low, where Indonesia is in the 9th lowest of 72 countries that took the PISA test. There are many aspects that can influence students' mathematical literacy skills, including cognitive styles and learning styles. The purpose of the study is to describe the profile of mathematical literacy based on cognitive styles and learning styles of students in grade VIII at SMP Buq'atun Mubarakah.  This study employed a descriptive research method through a qualitative approach. The data of the study were obtained by providing a mathematical literacy test in accordance with PISA standards, cognitive style test, and learning styles test. The data of students’ literacy test result were then explored through the interview process. The subjects of the study were students of SMP Buq'atun Mubarakah, namely one student with a field dependent cognitive style with a visual learning style, one student with a field dependent cognitive style with an auditory learning style, one student with a field dependent cognitive style with a kinesthetic learning style, one student with a field independent cognitive style with a visual learning style, one student with a field independent cognitive style with an auditory learning style, and one student with a field independent cognitive style with a kinesthetic learning style. Data validity testing was conducted by employing triangulation methods. The results of the study reveal that the subjects with different cognitive styles and learning styles each has characteristics and differences in working on literacy problems. These characteristics and differences include differences in identifying information, planning solutions, differences in carrying out the completion stage, checking work results, to differences in drawing conclusions.